Deteksi Salmonella spp pada pakan hewan laboratorium berbentuk pelet menggunakan Real Time Polymerase Chain Reaction (qPCR) dan Loop Mediated Isothermal Amplification (LAMP) - Fitra Yovita Delviona P; Puspita Dewi Fortuna; Nur Aini (Eruditio : Indonesia Journal of Food and Drug Safety, 2024)
Salmonella spp. contamination in animal feed is challenging for the commercial feed industry and laboratory animal facilities. Salmonellosis is a term used for Salmonella infection. Salmonellosis is a zoonosis directly transmitted to humans through contaminated feed, food, water, or infected animals. Nevertheless, infection in animals is mainly caused by contaminated feed. Since it provokes a significantly high economic loss due to its high mortality, accurate and rapid Salmonella detection methods are necessary for monitoring the quality of animal feed. The standard method for Salmonella detection in animal feed, which refers to ISO 6579, is based on the culture method, which takes about 5-7 days. Thus, an alternative method is required to give valid results faster. This study aims to develop alternative methods for Salmonella spp. detection in animal feed using Loop isothermal Amplification (LAMP) and Real-time Polymerase Chain Reaction (PCR) methods. Salmonella detection has been carried out on animal feed pellets artificially inoculated with Salmonella Typhimurium ATCC 14028 at three concentration levels, namely 1, 3, and 9 cfu per test portion (25-gram samples). e-LOD range values between the LAMP method and Real PCR are compared with the culture method and analyzed descriptively. Salmonella detection method using LAMP and Real-Time PCR showed the value e-LOD50 at 0.62 cfu/portion in mouse feed and e-LOD50 at 0.37 cfu/portion in rabbit feed. Compared to the LOD of the culture method, the e-LOD of LAMP and PCR showed similarity. This e-LOD value is the same as the e-LOD culture method. Related laboratories can utilize the results of this study to monitor the quality of animal feed.